2022
DOI: 10.31971/pps/145154
|View full text |Cite
|
Sign up to set email alerts
|

Social (in)security – the ambivalence of villagers' perceptions during COVID-19

Abstract: The aim of the study is to provide a subjective assessment of security in the social dimension of rural households during the COVID-19 pandemic. To achieve the objective, a four-stage primary study of households in Poland was designed and conducted. Subjective assessments of households' perceptions about social security are presented. The possibility of loss of financial stability, job loss and deterioration of the household situation was assessed. The respondents also assessed the possibility of a worsening o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The COVID-19 pandemic and resulting public health crisis had an enormous impact on the global economy at all scales and in all sectors, with disruptions affecting most types of economic activity [2][3][4][5][6][7][8][9][10][11][12], including related sectors such as logistics, transport, and energy [13][14][15][16]24]. While tourism and related activities, including food services, were most affected [20][21][22][23][24], agriculture was affected to varying degrees, depending on the scale, type, and nature of production and geographical location .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID-19 pandemic and resulting public health crisis had an enormous impact on the global economy at all scales and in all sectors, with disruptions affecting most types of economic activity [2][3][4][5][6][7][8][9][10][11][12], including related sectors such as logistics, transport, and energy [13][14][15][16]24]. While tourism and related activities, including food services, were most affected [20][21][22][23][24], agriculture was affected to varying degrees, depending on the scale, type, and nature of production and geographical location .…”
Section: Discussionmentioning
confidence: 99%
“…At the level of household income, cross-country evidence suggests that the poorest among the households benefited most from compensatory policy measures, while the disposable income of the best-placed households suffered less from containment measures [4][5][6]. Evidence from Malaysia indicated that households with low incomes were unaffected by pandemic restrictions or even benefited [7].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Human care during the COVID-19 pandemic imposed a complex set of actions and consequences on social policy (Daly, 2022). Furthermore, several Polish experts underline the impact of COVID-19 on social policy (Bieszk-Stolorz & Markowicz, 2022;Chłon ´-Domin ´czak et al, 2021;Kalinowski & Łuczak, 2021;Łaszek, 2020). Despite the relevance of these scientific works, they do not seek answers to the questions of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Some scientists indicate that these result from unproductive behaviour (Bertrand et al 2004), place of residence (Lichter et al 2012, Binder, 2014, Kalinowski 2015, Allard 2017, demographic reasons (Pearce, 1978;Lister 2007, Lewis & Campbell 2008, Cruz & Ahmed 2018, Ku et al 2018, individual disabilities (Sen, 1999, Emerson, 2007, or structural determinants (Brady 2019). An important cause is unfavourable random events (Krishna 2011), including the effects of the COVID-19 pandemic, which has been the main cause of poverty in the last two years, having had an extreme impact on the socio-economic situation (Kalinowski & Łuczak, 2021. On the other hand, Brady (2019) put the causes in three theoretical contextsbehavioural theories, structural theories and political theories.…”
Section: Introductionmentioning
confidence: 99%